The role of nurses in diabetes care and the impact of the different approaches of nurses role on patients percieved quality of nursing care: two case studies from the UK and Kuwait - Alshammari, Muna A. B. J. M. (2018)
Type 2 diabetes (T2D) is considered as a global major health problem, which requires healthcare systems to find solutions to meet the needs of the great numbers of people with T2D. One key to these solutions is nurses who undertake the provision of diabetes care. Nursing care in T2D varies across countries as a result of differences in healthcare systems, the way in which they are organised and other factors relating to nursing practice. The UK and Kuwait are two countries which have high incidences of T2D but differing health care delivery models, which has raised the need to understand the different roles of nurses in providing T2D care in these two countries’ healthcare systems. Key aims of this research were: (1) to investigate the actual roles undertaken by nurses in T2D care; (2) to investigate the extent to which these different roles affect perceived quality of nursing care; (3) to investigate the guidelines of diabetes care in the UK and Kuwait; and (4) to evaluate if nurses are delivering care based on these guidelines.